Financing Higher Education in Fiscal Year 2003: The State of the States - Mary P. McKeown-Moak (Educational Considerations, 2003)
So begins the 2002 Fiscal Survey of the States from the National Governors Association. Nearly every state has reduced budgets and cut expenditures in light of reductions in anticipated state revenues.